Paleoproterozoic (2.01 Ga) high-pressure granulite facies metamorphism and isothermal decompression of garnet-orthopyroxene-cordierite-orthoamphibole gneisses from the Central Zone of the Limpopo Belt in eastern Botswana - Brandt, Sönke; Klemd, Reiner; Ramos, Joshua; Drueppel, Kirsten; Xie, Hanqiang (Lithos, 2023)
The Central Zone (CZ) of the Limpopo Belt in southern Africa is a complex high-grade metamorphic zone that experienced a, in part, poorly understood poly-metamorphic history. To address this, we present petrological and SHRIMP U-Pb zircon age data for samples of a garnet-and orthopyroxene-bearing cordierite-orthoamphibole (Grt-Opx-Crd-Oam) paragneiss and a charnockite from the Baines Drift and the Phikwe Complexes, respectively. The two complexes are the north-western segments of the CZ in which the metamorphic history is poorly con-strained. High-pressure (HP) granulite facies metamorphism and a clockwise P-T evolution for the feldspar-free Grt-Opx-Crd-Oam gneiss of the Baines Drift Complex are constrained by the application of pseudosection modelling, Grt-Opx thermometry, and quartz in-garnet (QinG) elastic barometry. Our results show that the peak-metamorphic garnet-orthopyroxene-rutile-ilmenite-quartz assemblage formed at HP granulite facies conditions of >900 degrees C and 14 kbar, followed by significant decompression at granulite facies conditions, as recorded by conspicuous orthopyroxene-cordierite coronas around garnet. The widespread formation of orthoamphibole documents subsequent near-isobaric cooling into the amphibolite facies. Based on the formation of metamorphic zircon in the Grt-Opx-Crd-Oam gneiss we precisely determined an age of 2014 +/- 8 Ma for HP granulite facies metamorphism in the Baines Drift Complex. Rare detrital zircons document a possible deposition of the sedi-mentary protolith later than ca. 2.55 Ga, as part of a poorly documented Paleoproterozoic sediment sequence of the Central Zone. The clockwise P-T path and the age of HP granulite facies metamorphism in the Baines Drift Complex as constrained here, are consistent with constraints from 2.02 Ga metamorphism in the Beit Bridge Complex, the major segment of the CZ. The HP metamorphism is interpreted to reflect intracontinental Paleo-proterozoic transpressional orogeny within the consolidated Kaapvaal-Zimbabwe Craton. The association of lower-crustal HP granulite facies rocks of the Baines Drift Complex next to mid-crustal upper-amphibolite facies rocks of the Phikwe Complex may reflect progress of nappe tectonics during the Paleoproterozoic orogeny. SHRIMP U-Pb zircon data indicate that the granite protolith of the charnockite from the Phikwe Complex intruded at 2586 +/- 27 Ma, broadly synchronously with major granitoid emplacement in the Beit Bridge Com-plex. The similar P-T evolution of ca. 2.02 Ga metamorphism and comparable voluminous granite emplacement at ca. 2.6 Ga indicate a common evolution of the Baines Drift, the Phikwe and the Beit Bridge Complexes in the CZ of the Limpopo Belt.
CRIS-Team WoS Importer:2023-03-03